PENGGUNAAN METODE MIND MAPPING UNTUK KETERAMPILAN MEMBACA TEXT BAHASA JERMAN - Hamzah, Ryan Amirul; Wahyuningsih, Fahmi (LATERNE, 2022)
This research is basically motivated by the large number of students reading German texts. The ability to read is an important capital for a person’s personal life both in the school environment and outside the school environment. Because by reading someone can add new vocabulary and insights. This research is one way to find out how to use mind mapping for German reading skills for students. To achieve this goal, a literature study method is used. The use of the literature study method here is to find out in general the indicators used in mind mapping mapping in order to improve students’ reading skills. The results obtained in this study are that the mind mapping method is better applied after reading the text, this is because the making of mind mapping after reading the text can provide a global understanding so that it can help make mind mapping, besides the ideas obtained by students when finished reading can help to organize the making of mind mapping